2010
DOI: 10.1063/1.3467857
|View full text |Cite
|
Sign up to set email alerts
|

Plane and hemispherical potential structures in magnetically expanding plasmas

Abstract: Two-dimensional potential structures are measured for different gas pressure in expanding argon plasma using permanent magnets, where the magnetic field is about 100 G in the source and several gauss in the diffusion chamber. The plane potential drop is observed near the source exit for 0.35 mTorr, while the potential structure becomes hemispherical when increasing up to 1 mTorr; the hemispherical structure results in the radial divergence of the ion beam. It is found that the trajectories of the accelerated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…This behavior of the floating potential is similar to the one observed by Takahashi et al [16]. Figure 6C shows electron temperature from Langmuir probe (dots) and electron-RFEA (crosses).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…This behavior of the floating potential is similar to the one observed by Takahashi et al [16]. Figure 6C shows electron temperature from Langmuir probe (dots) and electron-RFEA (crosses).…”
Section: Resultssupporting
confidence: 70%
“…Later, others [14][15][16][17] have pointed out the 2D nature of the CFDL, in that the electrons follow the magnetic field lines and escape toward the side walls, while the non-magnetized ions follow a straight path from the source into the expansion chamber [18]. A curved 2D CFDL potential structure [19,20] and the conics of enhanced plasma density along the outermost magnetic fields emerging from the source region [21] has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of electron energy distributions have previously shown that the ion beam is electrically neutralized by the electrons being energetic in the source and overcoming the potential drop of the DL [2]. For further development of the propulsion device and for understanding the physics behind the DL formation, the radial and/or 2-D measurements have been progressed recently [3]- [5]. These investigations have suggested that the energetic electrons near the source wall move along the divergent field lines and ionize the neutrals in the diffusion chamber.…”
Section: Energetic Electrons Moving Along Peripheral Magnetic Field Lmentioning
confidence: 98%
“…It has been shown 4 that helicon sources can produce an interesting amount of thrust for that purpose, but experiments so far have used large electromagnets for the DC field, and these may be incompatible with the weight limits of spacecraft. The use of PM helicons for thrusters has already been investigated extensively by Takahashi et al 5,6,7 Their configuration of PMs is quite different from ours and does not use annular magnets. For thruster applications, that work is much more advanced than ours, since the ion energy distributions were measured in detail.…”
Section: Introductionmentioning
confidence: 99%